2017
DOI: 10.1111/bjh.14848
|View full text |Cite
|
Sign up to set email alerts
|

Combined intravitreal methotrexate and immunochemotherapy followed by reduced‐dose whole‐brain radiotherapy for newly diagnosed B‐cell primary intraocular lymphoma

Abstract: Primary intraocular lymphoma (IOL) has a propensity for central nervous system (CNS) relapse within 2 years of initial diagnosis, affecting clinical outcome. To reduce CNS relapse, we performed the combination treatment protocols of intravitreal methotrexate injections, methotrexate-based systemic induction chemotherapy and consolidation high-dose cytarabine and reduced-dose whole brain radiation therapy (rdWBRT, 23·4 Gy) for B-cell primary IOL with or without newly diagnosed CNS involvement. All patients unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 33 publications
2
42
0
Order By: Relevance
“…The two‐year CNS lymphoma‐free survival (CLFS) was 58.3%, whereas that of 8 patients treated with intravitreal MTX alone was 37.5%. Kaburaki et al combined intravitreal MTX injections, MTX‐based systemic induction chemotherapy, consolidation high‐dose cytarabine, and reduced‐dose whole‐brain radiation therapy (23 Gy) for the treatment of PVRL. Their study showed reduced CNS relapse (4‐year progression‐free survival: 72.7%; overall survival: 88.9%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two‐year CNS lymphoma‐free survival (CLFS) was 58.3%, whereas that of 8 patients treated with intravitreal MTX alone was 37.5%. Kaburaki et al combined intravitreal MTX injections, MTX‐based systemic induction chemotherapy, consolidation high‐dose cytarabine, and reduced‐dose whole‐brain radiation therapy (23 Gy) for the treatment of PVRL. Their study showed reduced CNS relapse (4‐year progression‐free survival: 72.7%; overall survival: 88.9%).…”
Section: Introductionmentioning
confidence: 99%
“…Their study showed reduced CNS relapse (4‐year progression‐free survival: 72.7%; overall survival: 88.9%). However, approximately 30% of patients still experienced CNS relapse . There is a strong necessity to establish a predictive marker for CNS disease development and risk stratification‐based treatment strategies for preventing the development of CNS disease.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that combination therapy combined with intraocular and systemic chemotherapy and radiotherapy of PIOL has improved clinical outcomes; with 4‐year OS rates of 75–86·3% (Lee et al , ; Kaburaki et al , ). However, SIOL have only been reported in several case reports with few integrated results.…”
mentioning
confidence: 99%
“…A smaller 2018 report from Charles University and General Hospital University (Prague, Czech Republic) provided additional data in support of a combined extensive and local treatment approach to VRL: in 10 patients with primary VRL, combined therapy with intravitreal methotrexate extended progression‐free survival, but not overall survival. Two non‐comparative studies from Japan involving 27 patients with VRL provide further support for combination treatment, including intravitreal methotrexate as ocular therapy, for primary VRL . While the best approach to managing VRL continues to be discussed, choice of treatment also will depend on general physical health and medical history, as noted in the 2015 European Association for Neuro‐Oncology Guidelines …”
Section: Role Of Intraocular Chemotherapy For Vitreoretinal Lymphomamentioning
confidence: 99%
“…Subsequent to the original clinical case series, medical centres in North America, Europe, the Middle East and Asia also have reported their experience in treating groups totalling at least 177 eyes of 114 patients with VRL, [34][35][36][37][38][39][40] as well as multiple individual patients, [41][42][43][44][45] using intravitreal methotrexate injections. Additional reports have described groups of patients suffering from VRL, who received a range of treatments that included methotrexate and/or rituximab intravitreal injections (see below).…”
Section: Intraocular Methotrexate Therapymentioning
confidence: 99%